RUANG PUBLIK KOTA DAN POLA KOMUNIKASI WARGANYA - Christoperus Herutomo (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
Arrangement of urban public space that takes into account social, cultural, economic andcharacteristic aspects of urban citizens will affect the pattern of urban citizens communication thatis anonymity. The anonymity nature of the citizens of this city is due to the very heterogin cityresidents consisting of ethnic background, religion, socioeconomic status and interests. Theanonymity of the townspeople causes a tendency for citizens to communicate with people orgroups with similar backgrounds and interests. Communication citizens who have the backgroundand interests of the same this will lead to the pattern of communication that is the primary ofpersonal communication, informal and expressive. This pattern of primary communication can beat the individual level such as family communication as well as group level such ascommunication in organizations that use city public space.